PENGARUH MANFAAT RELASIONAL TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK (Studi pada Bank BPD Bali Cabang Utama Denpasar) - Luh Putu Sri Wulandari Semadi; Ni Wayan Sri Suprapti; Ketut Nurcahya (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2012)
The Effect of Relational Benefits on Satisfaction and Loyalty of Bank’s Customer (Study on Denpasar Mainbranch of Bank BPD Bali). This study aims to determine (1) affect of relational benefits on bank’s customer satisfaction, (2) affect of relational benefits on bank’s customer loyalty, and (3) affect  of satisfaction on bank’s customer loyalty. There were 168 respondents in this research within their criteria are individualand trade enterprise which has become a customer of Bank BPD Bali in term of at least 1 (one) year.The sample deciding method are non probability sampling by combine purposive sampling and conveniencesampling. To gain the result as the research goal, Structural Equation Modelling (SEM) were analyzed by Analysis Moment of Structure (AMOS) an Special Package for Statistic Science (SPSS). The results shows that one of hypothesis not supported. Special treatment benefits has no significant affect on bank’scustomer satisfaction and loyalty. But both of relational benefits are confidence benefits and social benefits have positive and significant affect on bank’s customer satisfaction and loyalty. And the hypothesis thatcustomer satisfaction has positive and significant affect on bank’s loyalty customer is supported in this research